2016
DOI: 10.1080/0886022x.2016.1256313
|View full text |Cite
|
Sign up to set email alerts
|

Infective spondylodiscitis in patients on maintenance hemodialysis: a case series

Abstract: Infective spondylodiscitis is a rare disease. This case review describes the clinical course, risk factors, and outcomes of adult patients on maintenance hemodialysis who presented with infective spondylodiscitis at a single medical center in Taiwan. There were 18 cases (mean age: 64.9 ± 10.8 years) over more than 10 years. Analysis of underlying diseases indicated that 50% of patients had diabetes, 55.6% had hypertension, 55.6% had coronary artery disease, 22.2% had congestive heart failure, 22.2% had a cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
3
23
0
2
Order By: Relevance
“…Both combinations have adequate predictability for IS within future 1 month. Due to the natural rarity of IS [1, 7], there was limited sample size and it may be improper for us to add in more variables in light of it. However, based on our findings, we strongly suggest physicians to maintain a high degree of suspicion for infectious process facing symptoms of back pain, neurological deficit, unexplainable fever, weight loss, lethargy, or confusion in patients receiving maintenance HD, particularly if there has been an unexpected high ALP level, or inexplicable low RDW level following a recent access intervention in patients with relatively short HD vintage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both combinations have adequate predictability for IS within future 1 month. Due to the natural rarity of IS [1, 7], there was limited sample size and it may be improper for us to add in more variables in light of it. However, based on our findings, we strongly suggest physicians to maintain a high degree of suspicion for infectious process facing symptoms of back pain, neurological deficit, unexplainable fever, weight loss, lethargy, or confusion in patients receiving maintenance HD, particularly if there has been an unexpected high ALP level, or inexplicable low RDW level following a recent access intervention in patients with relatively short HD vintage.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of IS to prompt initiation of therapy is vital in ensuring successful treatment and preventing morbidity. Because of the insidious onset of IS symptoms and the fact that most of the specific changes in imaging tests require two to eight weeks after the onset of the infection, the diagnosis may be delayed and lead to serious complications including irreversible neurological deficits and death [7]. Thanks to the high sensitivities of serum markers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), they could serve as screening tests prior to magnetic resonance imaging (MRI), the gold standard to diagnose and evaluate the extent of IS [1].…”
Section: Introductionmentioning
confidence: 99%
“…Bosilkovski et al [33] showed that significantly-higher ESR was associated with osteoarticular brucellosis in univariate analysis. Another study found that a total of 78.6% of patients with infective spondylodiscitis had elevated ESR, and 55.6% had elevated levels of ALP [11].…”
Section: Discussionmentioning
confidence: 99%
“…Among osteoarticular complications, spondylodiscitis is a frequent and serious complication of brucellosis. Antibiotic treatment is mostly successful in early stages with no or minor neurological deficits; however, diagnosis may be delayed, due to the insidious onset of symptoms, development of abscess formation in the adjacent tissues, and disabiling neurological deficits [9][10][11]. Thus, early diagnosis is important.…”
Section: Introductionmentioning
confidence: 99%
“…Для инфекционных осложнений, возникших после операций (манипуляций) на позвоночнике, используют термин «инфекция области хирургического вмешательства на позвоночнике» (ИОХВп), соответствующий англоязычному понятию Surgical Site Infection in spinal surgery (SSIs). [20][21][22][23][24].…”
Section: термины и определенияunclassified